The Postcolonial Crescent - Deonna Kelli (International Institute of Islamic Thought, 1998)
Identity politics has become the catch phrase of the postmodern age. With concepts such as "exile," "migrancy," and "hybridity" acquiring unprecedented cultural significance in the late twentieth century, the postcolonial age gives way to new identities, fractured modes of living, and new conditions of humanity. Literature is a powerful tool to explore such issues in an era where a great deal of the world is displaced, and the idea of a homeland becomes a disrupted, remote possibility. The Postcolonial Crescent: Islam's Impact on Contemporary Literature, is an attempt to discuss how Muslims negotiate identity at a time of rapid and spiritually challenging transculturation. The book uses fiction written by Muslims to critique the effects of colonialism, counteract modernity, and question the status of Islamic identity in the contemporary world. It also can be considered as the primary introduction of contemporary Islamic literature into the postcolonial genre. Muslim writers have yet to submit a unique and powerful commentary on postcolonial and cultural studies; this work at least softens that absence. The Postcolonial Crescent was conceived as a response to The Satanic Verses controversy. Therefore, it is “intimately involved in the interchange between religion and the state, and demonstrates that the roles Islam is playing in postcolonial nation-building is especially contested in the absence of broadly acceptable models” (p. 4). Conflicting issues of identity are approached by interrogating the authority to define a “correct” Islamic identity, the role of individual rights, and the “variegation of Islamic expression within specific cultural settings, suggesting through the national self-definitions the many concerns that the Islamic world shares with global postcoloniality” (p. 7) ...